Otomatisasi Sistem Telemonitoring Perangkat Drip Irigation System Berbasis Iot Pada Daerah Pertanian Dataran Tinggi - Muhammad Anandri Hazim; Retno de; Okta Andrica Putra (Journal of Computer Scine and Information Technology, 2024)
Soil quality on agricultural land is one of the important things that needs special attention in its management. It is not easy to create ideal soil conditions for plants. For that, farmers need to know the variables that affect ideal conditions. The easiest way to find out the variables is to measure the pH and humidity of the soil conditions. designing and building an automatic drip irrigation system device. This system can be used as irrigation in highland agriculture. Therefore, in order for farmers to save water when the dry season comes, sophisticated technology is needed to minimize the risk of crop failure. The use of computer technology in the railroad crossing security system can be an optimal solution. This tool consists of Arduino Mega 2560 as the control center for all sensors, NodeMCU Esp8266 as a telemonitoring device, Soil moisture sensor as the key to this drip irrigation device can carry out irrigation connected to the Water Pump. In this study, a telemonitoring system will be created with telegrams on chili plant planting media based on soil acidity and soil moisture using the help of sensors that can be monitored online using the internet. Data will be stored in a database and displayed on the web. The results of the research on the planting media for chili plants obtained produced soil that is suitable for chili plants, namely sandy soil media that has a moisture value of 7 to 8 and a pH value of 6.5-7.5. The average time required to communicate between nodes to telegram is 344 ms, the process has moderate quality.